Alstonia scholaris in the ethnomedicinal and religious tradition of Coastal Karnataka, India - M Jayakara Bhandary (Society for Indonesian Biodiversity, 2020)
Abstract. MJ Bhandary. 2020. Alstonia scholaris in the ethnomedicinal and religious tradition of Coastal Karnataka, India. Biodiversitas 21: 1569-1577. The tribal and non-tribal indigenous communities of coastal districts of Karnataka use Alstonia scholaris (L.) R. Br. for the treatment of various ailments such as fever, asthma, leucorrhea, eczema, indigestion and also to heal spider bites. An annual health-related ritual of mass drinking of a bitter juice or decoction of the stem bark of this tree on the new moon (amavasya) day of ‘aati’ month of the traditional ‘tulu’ calendar coinciding with the rainy monsoon season is popularly followed in the study area, especially by the rural families. The underlying belief is that this drink keeps away all ailments and ensures wellbeing. The recorded ethnomedicinal uses and the traditional practice of mass drinking of the bitter juice appear to be scientifically meaningful when interpreted on the background of the ayurvedic uses and the wide range of curative properties ascribed to this plant, many of which have been confirmed by reported pharmaco-chemical studies. Studies have also indicated that the toxicity of the bark extract was minimum during monsoon season and the concentration of active principle was maximum in the bark juice collected on the particular new moon day. This further justifies the timing of the described annual medicine drinking event. In addition, some Tulu language-speaking indigenous communities consider this tree as the reincarnation of a mythological demon called Bali and worship its branch during the festival days of Deepavali, in honor of him. Thus, A. scholaris emerges as a plant of great ethnobotanical significance in the study area.